Nonhuman primate models of pediatric viral diseases - Vijayan K. K., Vidya; De Paris, Kristina (Frontiers in Cellular and Infection Microbiology, 2024)
Infectious diseases are the leading cause of death in infants and children under 5 years of age. In utero exposure to viruses can lead to spontaneous abortion, preterm birth, congenital abnormalities or other developmental defects, often resulting in lifelong health sequalae. The underlying biological mechanisms are difficult to study in humans due to ethical concerns and limited sample access. Nonhuman primates (NHP) are closely related to humans, and pregnancy and immune ontogeny in infants are very similar to humans. Therefore, NHP are a highly relevant model for understanding fetal and postnatal virus-host interactions and to define immune mechanisms associated with increased morbidity and mortality in infants. We will discuss NHP models of viruses causing congenital infections, respiratory diseases in early life, and HIV. Cytomegalovirus (CMV) remains the most common cause of congenital defects worldwide. Measles is a vaccine-preventable disease, yet measles cases are resurging. Zika is an example of an emerging arbovirus with devastating consequences for the developing fetus and the surviving infant. Among the respiratory viruses, we will discuss influenza and Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2). We will finish with HIV as an example of a lifelong infection without a cure or vaccine. The review will highlight (i) the impact of viral infections on fetal and infant immune development, (ii) how differences in infant and adult immune responses to infection alter disease outcome, and emphasize the invaluable contribution of pediatric NHP infection models to the design of effective treatment and prevention strategies, including vaccines, for human infants.